45.4k views
5 votes
-5 1/2 -4 1/4 - 6 3/4

1 Answer

2 votes

For this case we have an expression of mixed numbers:


5 \frac {1} {2} = \frac {2 * 5 + 1} {2} = \frac {11} {2}\\4 \frac {1} {4} = \frac {4 * 4 + 1} {4} = \frac {17} {4}\\6 \frac {3} {4} = \frac {4 * 6 + 3} {4} = \frac {27} {4}

Rewriting the expression we have:


- \frac {11} {2} - \frac {17} {4} -\frac {27} {4} =

Remember that equal signs are added and the same sign is placed.


- \frac {11} {2} - \frac {44} {4} =\\- \frac {11} {2} - \frac {22} {2} =\\- \frac {33} {2}

Answer:


- \frac {33} {2}\\-(15 \frac {3} {2})

User Vijay Murthy
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.